Dominasi Kuasa Wacana Terhadap Eksistensi Crossplayer di Ruang Privat-Publik Dunia Maya - Asep Achmad Muhlisian; Dian Rizky Azhari (Universitas Diponegoro, 2022)
This study discusses the dominance of the power on the existence of crossplayer in the private-public space of cyberspace. The subjects of this study were four respondents consisting of 2 female to male (F2M) crossplayers and 2 male to female (M2F) crossplayers. This study uses a critical discourse analysis approach to reveal cultural phenomena using Sartre's concept of Being and Foucault's concept of the power of discourse. The results of this study indicate that crossplay in Indonesia is not an easy thing to do. The rejection from the community is quite large because of the negative stigma for cross-dressed people. Crossplay actors have to disguise their identities on social media and operate clandestinely, as a form of their negotiation against the power of the majority discourse who rejects their existence. They also form a community so that they still have a place to actualize their hobby. The creation of a community is also a protective area for various crossplay activities from the power of the majority discourse. Their activities on social media are still carried out in these conditioned public spaces, because the followers are people who like Japanese culture who support crossplay discourse. <a href=